Persepsi dan Minat Mahasiswa Jurusan Akuntansi TerhadapMata Kuliah Akuntansi Syariah - Rika Amelia; Wirman Wirman (Peneliti.net, 2023)
This research aims to find out how the perceptions and interests of students majoring in accounting towards sharia accounting courses. For this study using a qualitative method approach. The location of this research was conducted at the Faculty of Economics and Business of Karawang Singaperbangsa University. And for data collection using a questionnaire and distributed to 50 respondents. Testing this hypothesis using regression analysis. The result is that simultaneously student perceptions and student interests have a significant effect on sharia accounting courses. Partially, student perceptions and student interests have a positive effect on sharia accounting courses.